1993
DOI: 10.1101/gad.7.4.583
|View full text |Cite
|
Sign up to set email alerts
|

The yeast SNF2/SWI2 protein has DNA-stimulated ATPase activity required for transcriptional activation.

Abstract: The yeast SNF2 (SWI2) protein functions with SNF5, SNF6, SWI1, and SWI3 in the transcriptional activation of many differently regulated genes. These proteins appear to facilitate activation by gene-specific regulatory proteins. SNF2 is highly conserved among eukaryotes and defines a family of proteins with similarity to helicases and nucleic acid-dependent NTPases. Here, we present genetic and biochemical evidence that SNF2 has DNA-stimulated ATPase activity. Mutations in the nucleoside triphosphate (NTP)-bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
212
1
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 285 publications
(224 citation statements)
references
References 51 publications
9
212
1
2
Order By: Relevance
“…This motif was ®rst described following the cloning of the brahma (brm) gene in drosophila (Haynes et al, 1992;Tamkun et al, 1992) and has since been identi®ed in other transcriptional co-activators including the human brahma protein, BRM (Muchardt and Yaniv, 1993) and the yeast protein SNF2/SWI2 (Laurent et al, 1993). The cell cycle gene 1 (CCG1) (Sekiguchi et al, 1991) which was later identi®ed as hTAF II 250 (Hisatake et al, 1993;Ruppert et al, 1993) and shown to be necessary for G1 progression in mammalian cells also contains a bromodomain.…”
Section: Discussionmentioning
confidence: 99%
“…This motif was ®rst described following the cloning of the brahma (brm) gene in drosophila (Haynes et al, 1992;Tamkun et al, 1992) and has since been identi®ed in other transcriptional co-activators including the human brahma protein, BRM (Muchardt and Yaniv, 1993) and the yeast protein SNF2/SWI2 (Laurent et al, 1993). The cell cycle gene 1 (CCG1) (Sekiguchi et al, 1991) which was later identi®ed as hTAF II 250 (Hisatake et al, 1993;Ruppert et al, 1993) and shown to be necessary for G1 progression in mammalian cells also contains a bromodomain.…”
Section: Discussionmentioning
confidence: 99%
“…Other DEAD box proteins could perform functions distinct from RNA unwinding. These possible functions include (1) mediating larger scale RNA structural rearrangements (Figure 10b) (38)(39)(40); (2) altering protein-RNA or protein-protein interactions, analogous to the disruption of protein-DNA contacts in the nucleosome by the Swi/Snf complex ( Figure 10c; the ATPase of the Swi/Snf complex, Swi2/Snf2, is related to the DEAD box family (41,(42)(43)(44)(45)); and (3) functioning, as the G-protein EF-Tu does, as a guarantor of fidelity in RNA-RNA interactions and rearrangements (46). There is no reason to assume a priori that all members of a sequence family of proteins perform the same function.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, this complex is composed of more than 10 subunits, and each of the complex contains a single molecule of either Brm or BRG1, but not both (Wang et al, 1996). These two proteins are the catalytic subunits and have DNA-dependent ATPase activity that drives remodeling of nucleosomes (Laurent et al, 1993). We previously reported that Brm and BRG1 have clear differences in their biological activities; Brm is essential for maintenance of murine leukemia virus (MuLV)-based retroviral gene expression, whereas BRG1 is not (Mizutani et al, 2002).…”
Section: Introductionmentioning
confidence: 99%